EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MEMBANGUN MORAL SISWA - erik pernando siregar; rahel irania; khuslul khoiriyah putri; rafli hidayat; Annisa’shonia Rahma; aji pangestu; ami latifah (UNISAN JURNAL, 2023)
This research examines how Islamic religious education improves students’ morals in private junior high schools. This research aims to find out: 1. To find out how Islamic religious education improves students’ morals in private junior high schools. Find the labels of students’ drinks and beverages. Researchers conducted naturalistic qualitative research. Without manipulating the subjects being studied, researchers make observations and collect data naturally. Based on the results of research conducted by researchers, it can be concluded that the implementation of Islamic religious education has gone well, as can be seen from the students’ activeness during the learning process and the majority of students can understand the material presented by the Islamic religious education teacher. However, despite this, there are still a small number of students who eat and drink according to Islamic eating and drinking etiquette.